Análise da efetividade das decisões judiciais de medida de segurança na modalidade de internação no estado do Tocantins - Costa, Bernardino Cosobeck da (Universidade Federal do Tocantins, 2015)
This thesis is an analysis of the dichotomy between theory and practice in the application of the security measure of hospital in the State of Tocantins through historic-philosophical and inductive method under the qualitative prism. To this end, we carried out a revision of theoretical literature as Michel Foucault, Giorgio Agamben, Tarsis Barreto among others, committed to the philosophical approach, historical, sociological and anthropological. As the core of the study came from the case analysis of lawsuits that mental patients undergoing tocantinense prison system. So, what is sought is not prejudice the field of subjectivity is correct or not, the (in) applicability of the security measure of hospitalization, but rather seek what is moving such (in) applicability in the way it is. In the liberal system who do not mobilize or claims in the social group does not exist, and worse, that does not apply to the market is put to the social margin. In this mainstay, we can speak of the non-democratic representation, especially noticeable in the popular demonstrations that occurred between the years 2013 and 2014 in Brazil, syndrome however, it is possible to broaden understanding of such breach of government representation in groups with higher dissociation or higher degree of fragmentation before party groups as in the case of mentally ill criminals. Thus, this thesis seeks to understand which system veridição or strategic discourse is permeating the (in) applicability of security measures hospitalization in Tocantins. At the end, we sought to bring concrete proposals aimed at safeguarding the fundamental rights of the mentally ill offender in the state of Tocantins.